Suicidality in Women with Adjustment Disorder and Depressive Episodes Attending an Irish Perinatal Mental Health Service - Doherty, Anne M (Int J Environ Res Public Health, 2019)
Depression is common in the perinatal period, with prevalence rates of 14.4%, but prevalence rates of adjustment disorder in this period have not been established. We aimed to examine the characteristics of women attending a perinatal psychiatry service diagnosed with adjustment disorder (AD) or depressive episodes (DE). The data were collected as part of a multicentre case-control study of 370 patients, 45 of whom were recruited from perinatal psychiatry service at a maternity hospital. We recruited 45 patients with AD or DE diagnosed in the perinatal period and compared them to a matched sample of 109 non-perinatal women. Almost half, 22 (48.9%) perinatal women had a diagnosis of AD and 23 (51.1%) had a diagnosis of DE. Of the perinatal participants, those with AD had more stressful life events, and suicidal ideation and behaviours were three times more common (31.8%) in AD than in DE (8.7%). There were no significant differences in levels of suicidality between the perinatal and the non-perinatal groups. In our cohort, AD is associated with symptoms of depression including suicidal ideation during the perinatal period. Further study is required to examine the relationship between stressors and suicidality in this population.